A novel strategy for Au in food science: Nanoformulation in dielectric, sensory properties, and microbiological quality of fish meat. (June 2021) - Çetinkaya, Turgay; Ceylan, Zafer; Meral, Raciye; Kılıçer, Ali; Altay, Filiz
Abstract: Fabrication of Au-zein-based nanomats (AuZ-Nm) was successfully carried out by using the electrospinning technique. The average diameters of Au were found as 530 ± 377 nm within zein nanomats having 161 ± 45 nm. The nanomats were used to delay the Total Mesophilic Aerobic Bacteria (TMAB) growth in the skinless fish fillets stored at 4 ± 1°C. Besides control samples, dielectric properties (ε′ and ε'') of the skinless fish fillets treated with AuZ-Nm were revealed. During the 8-days-storage, sensory changes in the samples treated with AuZ-Nm were determined. Microbiological test demonstrated that the use of AuZ-Nm limited the TMAB growth up to ~1 log CFU/g (p < 0.05). ε′ values of the fish samples treated with AuZ-Nm (changes from 76.47 to 54.29) were more stable as compared to untreated fish samples (p < 0.05). The changes in ε'' for control and nanotreated samples were 86.94% and 77.92%. The overall acceptability of the nanotreated samples was higher than the control samples. The stability of dielectric properties, limitation of microbiological spoilage, and also delaying of sensory deterioration of the fish fillets could be provided by using AuZ-Nm. In this respect, the use of Au-zein-based nanomats in the present study with the results could be playing a guiding role for further food studies. Graphical abstract: Image 1 Highlights: Au-zein-based electrospun nanomats were successfully fabricated by electrospinning technique. 530 nm-Au within zein (AuZ) nanomats having 161 nm was obtained. AuZ-nanomats provided higher dielectric stability (ε′ and ε'') in fish fillets. Sensory deterioration in fish fillets stored at 4 ° C was limited by using AuZ-nanomats. Microbiological stability tests revealed almost 1 log CFU/g limitation.